Academic Dishonesty in Online Learning During the COVID-19 Pandemic: The Role of Gender, Moral Self-Concept, and Academic Self-Efficacy - Intishar, Ivana Nur; Ampuni, Sutarimah; Buwono, Sukmo Bayu Suryo (Jurnal Psikologi, 2024)
This study aimed to examine the role of gender, moral self-concept, and academic self-efficacy on academic dishonesty among students during periods of online learning. Participants were 305 students aged 18-24 (male = 65, female = 240) who underwent online learning during the COVID-19 pandemic. This study used a survey method conducted online. The measuring instruments used were the Academic Dishonesty Scale to measure academic dishonesty, the Academic Self-Efficacy Scale to measure academic self-efficacy, and the Moral Self-Concept Scale to measure moral self-concept. Males indicated a higher tendency to commit academic dishonesty than females. The initial results of regression analysis showed that moral self-concept predicted academic dishonesty in a negative direction, while academic self-efficacy did not show a significant contribution toward academic dishonesty. Follow-up regression analysis was conducted by entering the two aspects of academic self-efficacy separately into the model, and it was found that while course efficacy did not show a significant contribution toward academic dishonesty, social efficacy contributed significantly in a positive direction.